Pengaruh Financial Distress dan Good Corporate Governance pada Praktik Tax Avoidance - Cita, I Gede Ambara; Supadmi, Ni Luh (E-Jurnal Akuntansi, 2019)
Efforts to minimize tax payments from nominal should be legally called tax avoidance. This study aims to examine the effect of financial distress and good corporate governance on tax avoidance that is proxied by the cash effective tax rate (CETR). This research was conducted in the consumer goods sector companies listed on the Indonesia Stock Exchange in 2013-2017. Determination of the number of samples using purposive sampling method and obtained a sample of 105 samples. Data were analyzed using multiple linear regression analysis. Based on the results of the analysis found financial distress has a negative effect on tax avoidance, institutional ownership has a positive effect on tax avoidance, independent commissioners have a positive effect on tax avoidance, and audit committees have a positive effect on tax avoidance. Keywords : Financial Distress; Institutional Ownership; Independent Commissioner; Audit Committee; Tax Avoidance.